2016
DOI: 10.1590/0103-6440201601110
|View full text |Cite
|
Sign up to set email alerts
|

Adhesives Doped with Bioactive Niobophosphate Micro-Filler: Degree of Conversion and Microtensile Bond Strength

Abstract: To evaluate the effect of incorporating niobium phosphate bioactive glass (NbG) into commercial etch-and-rinse adhesive systems, with and without silane, on their degree of conversion (DC) (%) and microtensile bond strength (μTBS). The NbG micro-filler was added to two etch-and-rinse adhesive systems: One Step (OS) and Prime & Bond (PB) at 40% concentration. The following groups were formed: control without glass addition OS; addition of unsilanized NbG (OSNbG); addition of silanized NbG (OSNbGS); control with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…A total 20 studies [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111] was found as per the inclusion criteria, whereby seven studies 92,[94][95][96]98,106,108) were based on fluoride-based bioactive glass (F-BAG). Few studies showed doping of zinc 101,102,107) , silver 110) , and niobiophosphate 109) in BAG powders. Experimental dental adhesives were also prepared by adding mineral trioxide aggregate (MTA) in BAG powder 103,104) .…”
Section: Acpmentioning
confidence: 99%
“…A total 20 studies [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111] was found as per the inclusion criteria, whereby seven studies 92,[94][95][96]98,106,108) were based on fluoride-based bioactive glass (F-BAG). Few studies showed doping of zinc 101,102,107) , silver 110) , and niobiophosphate 109) in BAG powders. Experimental dental adhesives were also prepared by adding mineral trioxide aggregate (MTA) in BAG powder 103,104) .…”
Section: Acpmentioning
confidence: 99%
“…This could be accounted for by the high degree of conversion obtained with a high glass percent where the intensity of the CuO peak would be high. The degree of conversion of the unfilled adhesive is similar to that obtained by Carneiro et al . It is, however, lower than that obtained by Ito et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although this proposal involves an additional step that causes an increase in clinical time, it may protect the integrity of the adhesive interface over time. Other proposals, such as the use of sonic devices [8]; application of multiple layers [9] and use of bioactive substances [10,11]; are found in the literature, but their ability to maintain bond strength (BS) longevity has not been conclusively proved.…”
Section: Introductionmentioning
confidence: 99%